Effect of Dietary Components from Antarctic Krill on Atherosclerosis in apoE-Deficient Mice - C. Parolini; Bjorndal, Bodil; M. Busnelli; S. Manzini; G.S. Ganzetti; F. Dellera; Ramsvik, Marie; Bruheim, Inge; Berge, Rolf Kristian; G.M. Chiesa (Molecular Nutrition & Food Research, 2017)
SCOPE: Antarctic krill is a great source of n-3 fatty acids and high-quality proteins. Aim of the study was to evaluate the effect of Antarctic krill components on plasma lipids and atherosclerosis development. METHODS AND RESULTS: Sixty apoEKO mice were divided into four groups and fed Western diet (CONTROL) or Western-like diets, differing for protein or fat content. Specifically, casein or fat in CONTROL was partially replaced by krill proteins (PRO), krill oil (KRILL OIL), or both (KRILL OIL+PRO). In KRILL OIL+PRO and KRILL OIL, cholesterol levels were significantly lower than in CONTROL group. Atherosclerosis in aorta of PRO, KRILL OIL and KRILL OIL+PRO was lower than in CONTROL, whereas, at the aortic sinus, atherosclerosis reduction was only observed in KRILL OIL. Liver steatosis, commonly present in CONTROL and PRO animals, was sporadic in KRILL OIL+PRO and KRILL OIL mice. Krill oil containing diets affected the expression of genes involved in cholesterol metabolism, mainly HMG-CoA reductase. No reduced systemic inflammation was found in all groups. CONCLUSION: Krill oil containing diets were able to reduce cholesterol levels, inhibit plaque development and prevent liver damage. Krill proteins also reduced atherosclerosis development through mechanisms not involving lipid metabolism.